Effectiveness of Two-tier Multiple Choice Diagnostic Test for Analyzing Students' Misconceptions in High School Physics Learning - Nuning Rohmantika; Eko Setyadi Kurniawan; Sriyono Sriyono (Radiasi : Jurnal Berkala Pendidikan Fisika, 2022)
Physics is a subject related to the environment so that it requires students to study nature and apply it in life. However, in learning sometimes students have difficulty understanding physics concepts and cause students to experience misconceptions. Therefore, a two-tier multiple choice diagnostic test is needed to analyze students' misconceptions. This study aims to determine the effectiveness of the two-tier multiple choice diagnostic test to analyze students' misconceptions in terms of content validity, practicality, and effectiveness. The research model is instrument development. The research design used is true experiment research with pretest posttest control. The subject of this research is class X MIPA MA Negeri Purworejo. Data collection in this study used validation sheets, observation sheets, student response questionnaires, and two-tier multiple choice diagnostic tests. The results showed that: 1) content validation for the construct and language aspects obtained from 3 validators got an Aiken V index of 1 for all items included in the high validity category, 2) a practical two-tier multiple choice diagnostic test in terms of sheets. observations with reliable categories and good responses and responses from students, 3) student learning outcomes have increased with an N-gain of 0.5 which is included in the medium category and students' misconceptions are found on the subject of momentum, impulse, and collision by 41.20% which is at medium level. Thus the two-tier multiple choice diagnostic test is declared valid, practical, and effective so that it is feasible to analyze students' misconceptions in learning physics.